Numerical Approach for the Controllability of Composite Fractional Dynamical Systems - Govindaraj, Venkatesan; Balachandran, Krishnan; George, Raju K (Journal of Applied Nonlinear Dynamics, 2026)
This paper deals with the numerical computations for the controllability of linear and nonlinear composite fractional dynamical systems. The goal is to compute a control state that drives the system from a prescribed initial state to described final state in a large enough controllability time. We address the controllability results using Grammian matrix and iterative technique. Some examples are provided to illustrate the results.